Medical Characteristics of Arid-Semi Arid Truffle Terfezia and Picoa in the Elazığ-Malatya region of Turkey ? - Akyüz, Mehmet; Kırbağ, Sevda; Bircan, Burak (Hacettepe Üniversitesi, 2015)
In this study, the antimicrobial and antioxidant activity of Terfezia boudieri, T. claveryi, T. olbiensis, Picoa le- febvrei and P. juniperi were investigated. It was determined that the methyl alcohol extraction of T. boudieri, T. claveryi, T. olbiensis, P. lefebvrei and P. juniperi inhibit the development of E. coli, B. subtilis, P. aeruginosa, S. aureus, S. mutans, P. vulgaris, S. typhi, C. tropicalis and Trichophyton sp. at various levels 8 mm to 22 mm diameter and their effect to remove the DPPH radical was more efficient at groups to which samples of 25 ?L 1.22% to 2.58% , 50 ?L 2.31% to 3.28% and 100 ?L 5.24% to 8.00% were added. It was determined that methyl alcohol that was extracted from Terfezia species were more effective than Picoa species against test microorganisms. When the groups were compared in terms of concentration, the highest level of free radical scavenging effect at the group, to which we added a 100 ?L sample, was seen at T. boudieri with 8.00%.

B u çalışmada, Terfezia boudieri, T. claveryi, T. olbiensis, Picoa lefebvrei ve P. juniperi’nin antimikrobiyal ve antioksidant özellikleri araştırıldı. T. boudieri, T. claveryi, T. olbiensis, P. lefebvrei ve P. juniperi’nin metil alkol özütlerinin; E. coli, B. subtilis, P. aeruginosa, S. aureus, S. mutans, P. vulgaris, S. typhi, C. tropicalis ve Trichophyton sp.’nin gelişmelerini değişik oranlarda 8-22 mm çap inhibe ettiği ve DPPH radikalini giderme etkisinin ise 25 ?L % 1.22-2.58 , 50 ?L % 2.31-3.28 ve 100 ?L % 5.24-8.00 örnek eklenen gruplarda daha etkili olduğu tespit edilmiştir. Terfezia türlerinden elde edilen metil alkol özütlerinin, test mikroorganizmalarına karşı Picoa türlerinden daha etkili olduğu tespit edilmiştir. Derişime bağlı olarak gruplar karşılaştırıldığında ise 100 ?L örnek eklediğimiz grupta en fazla serbest radikal giderme etkisi % 8.00 ile T. boudieri’de görülmektedir
Türkiye’nin Elazığ-Malatya Çevresindeki Kurak-Yarı Kurak Trüflerin Tıbbi Özellikleri